THE FEMININE AND THE CATHOLIC MUSIC: BETWEEN PRACTICES AND REPRESENTATIONS - Simoes Duarte, Fernando Lacerda [UNESP] (Univ Estadual Paulista Julio Mesquita Filho, Fac Ciencias Humanas & Sociais, 2018)
Effeminate and feminine were recurrent expressions in documents and theological writings that sought to discipline musical practices in the Roman Catholic Church, characterizing the degeneration of the character through music. This paper seeks to understand the fundamental of this representation, as well as the female presence or absence in Brazilian musical practices. Data obtained in bibliographical and documentary research were analyzed from the references of memory and identity in Joel Candau, as well as of practices and representations, by Roger Chartier. The results point to attempts to silence the feminine in religious music literally and symbolically. However, the presence of women in Brazilian musical practices was recurrent, according to musical documents collected from various collections.
Keywords: Religious Music; Roman Catholic Church; Music and gender; Patristic; Theatrical music; Effeminate music